THE MATHEMATICAL DESCRIPTION OF THE FORCE OF INTERACTION BETWEEN WHEELS AND RAILS - Dehtiaryova, L. N.; Osenin, Yu. I.; Myamlin, S. V. (Science and Transport Progress, 2009)
In the article the mathematical description of force interaction of wheels and rails is offered as well as the description of some indices of traffic safety of rail vehicles is performed.